2010
DOI: 10.1016/j.jcss.2010.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Towards a dichotomy for the Possible Winner problem in elections based on scoring rules

Abstract: To make a joint decision, agents (or voters) are often required to provide their preferences as linear orders. To determine a winner, the given linear orders can be aggregated according to a voting protocol. However, in realistic settings, the voters may often only provide partial orders. This directly leads to the Possible Winner problem that asks, given a set of partial votes, whether a distinguished candidate can still become a winner. In this work, we consider the computational complexity of Possible Winne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 25 publications
2
66
0
Order By: Relevance
“…Conversely, relays in track and field (especially the 4 × 400) approximately satisfy Axiom 5. 14 Young (1995) includes an intuitive introduction; among the many more recent examples, Davenport andKalagnanam (2004), or Betzler andDorn (2010); Davenport and Kalagnanam (2004).…”
Section: The Index M and The Kendall-tau Distancementioning
confidence: 99%
“…Conversely, relays in track and field (especially the 4 × 400) approximately satisfy Axiom 5. 14 Young (1995) includes an intuitive introduction; among the many more recent examples, Davenport andKalagnanam (2004), or Betzler andDorn (2010); Davenport and Kalagnanam (2004).…”
Section: The Index M and The Kendall-tau Distancementioning
confidence: 99%
“…Xia and Conitzer showed that, for unweighted votes and an unbounded number of candidates, for most commonly used voting rules computing possible winners is NP-hard, whilst computing necessary winners is coNP-hard for some voting rules but polynomial for others [38]. Also, Betzler and Dorn [3,4], and Baumeister and Rothe [2], showed that, for an unbounded number of candidates and unweighted votes, computing possible winners is NP-hard for some classes of scoring rules and polynomial for others.…”
Section: Incomplete Profiles Possible and Necessary Winnersmentioning
confidence: 99%
“…Let P be an incomplete profile, A is a possible winner for M(P) and r if there exists a completion M of M(P) such that 4 respectively the set of possible and necessary winners for M(P) and r . Note that these notions of possible and necessary winners only apply to rules that are based on the majority graph.…”
Section: Examplementioning
confidence: 99%
See 2 more Smart Citations